Peritoneal Dialysis Care in Mainland China: Nationwide Survey - Ping Li; Xueying Cao; Weicen Liu; Delong Zhao; Sai Pan; Xuefeng Sun; Guangyan Cai; Jianhui Zhou; Xiangmei Chen (JMIR Publications, 2023)
BackgroundPeritoneal dialysis (PD) care in mainland China has been progressing in the past 10 years. ObjectiveTo complement information from the dialysis registry, a large-scale nationwide survey was conducted to investigate the current infrastructure and management of PD care at hospitals of different tiers. MethodsA web-based multiple-choice questionnaire was distributed through the National Center for Nephrology Medical Quality Management and Control to PD centers of secondary and tertiary hospitals in October 2020. The 2-part survey collected the information of PD centers and the clinical management of patients on PD. A total of 788 effective surveys from 746 hospitals were voluntarily returned, and data were extracted and analyzed. ResultsThe effective survey data covered 101,537 patients on PD, with 95% (96,460/101,537) in the tertiary hospitals. The median number of patients per PD center was 60 (IQR 21-152); this number was 32 (IQR 8-65) and 70 (IQR 27-192) for secondary and tertiary hospitals, respectively. There was a discrepancy in the availability of designated physical areas for different functions of PD care between the secondary and tertiary hospitals. The proportion of tertiary hospitals with PD training (P=.01), storage (P=.09), and procedure area (P<.001) was higher compared to secondary hospitals. PD catheter placement was performed in 96% (608/631) of the PD centers in tertiary hospitals, which was significantly higher compared to 86% (99/115) in secondary hospitals (P<.001). Automated PD was available in 55% (347/631) of the tertiary hospitals, which was significantly higher than that in secondary hospitals (37/115, 32%) according to the survey (P<.001). The most commonly performed PD module was continuous ambulatory peritoneal dialysis (772/788, 98%), followed by intermittent peritoneal dialysis (543/788, 69%). The overall reported nocturnal intermittent peritoneal dialysis was 31% (244/788); it was 28% (220/788) for continuous cycling peritoneal dialysis and 15% (118/788) for tidal peritoneal dialysis. Comparisons between the secondary and tertiary hospitals revealed no significant differences in prophylactic antibiotic use for PD catheter placement and therapeutic use for peritonitis. The first peritoneal equilibrium test was conducted in 58% (454/788) of patients at 4-6 weeks after initiation of PD, and 91% (718/788) reported at least one peritoneal equilibrium test per year. Overall, 79% (570/722) and 65% (469/722) of PD centers performed assessment for dialysis adequacy and residual kidney function, respectively; and 87% (685/788) of patients on PD were followed every 1 to 3 months for laboratory and auxiliary examinations. ConclusionsThis national survey reflects the current status and disparities of PD center management in mainland China. The study results suggest that the PD care needs to be more conveniently accessible in secondary hospitals, and quality management and staff training in secondary hospitals are still in high demand.